Scaling readiness: Concepts, practices, and implementation - Sartas, Murat; Schut, Marc; Schagen, Boudy van; Thiele, Graham; Proietti, Claudio; Leeuwis, Cees (International Potato Center, 2020)
Scaling Readiness is an approach that can support organizations, projects, and programs in achieving their ambitions to scale innovations and achieve impact. Scaling Readiness encourages critical reflection on how ready innovations are for scaling, and what appropriate actions could accelerate or enhance scaling.